Unveiling Progress in Sustainable Tourism Research: A Comprehensive Bibliometric Exploration - Singh, Swati; Ahmad, Mansoor; Siraj, Sadaf (Turizam, 2025)
Purpose: This research aims to evaluate the contribution of studies on sustainable tourism to the existing body of literature in this field.Design/Methodology/approach: A comprehensive analysis of 1310 literary works was conducted using bibliometric analysis. The study followed the parameters outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework, with a primary focus on the Scopus database. The study also emphasizes the importance of accurately identifying authors, references, and links relevant to sustainable tourism research.Findings: The analysis reveals the progression of research in sustainable tourism and identifies key co-citation clusters within the field. It highlights the absence of bibliometric analysis in this sector and underscores the need for fostering research collaboration between developed and developing nations to facilitate the development of sustainable tourism policies.Originality: This study provides a comprehensive examination of the literature on sustainable tourism, employing bibliometric analysis to fill the gap in existing research. By identifying key co-citation clusters and emphasizing the importance of research collaboration, this study offers original insights into the field of sustainable tourism.